2020
DOI: 10.3390/nu12061795
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Skin Microbiome, Pro- and/or Pre-Biotics to Affect Local Cutaneous Responses to UV Exposure

Abstract: The human skin hosts innumerable microorganisms and maintains homeostasis with the local immune system despite the challenges offered by environmental factors such as ultraviolet radiation (UVR). UVR causes cutaneous alterations such as acute (i.e., sunburn) and chronic inflammation, tanning, photoaging, skin cancer, and immune modulation. Phototherapy on the other hand is widely used to treat inflammatory skin diseases such as psoriasis, atopic dermatitis, polymorphic light eruption and graft-versus-host dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 132 publications
0
40
0
Order By: Relevance
“…The skin hosts trillions of microorganisms which can influence its homeostasis, in combination with other environmental and genetic factors [ 45 ]. Probiotics have been shown to exert protective effects against skin carcinogenesis, by reversing ultra-violet radiation induced damage [ 46 ]. In the present study, we investigated the direct antiproliferative activity of L. paracasei AGR 4 against the human melanoma cell line, A375, employing the SRB assay.…”
Section: Resultsmentioning
confidence: 99%
“…The skin hosts trillions of microorganisms which can influence its homeostasis, in combination with other environmental and genetic factors [ 45 ]. Probiotics have been shown to exert protective effects against skin carcinogenesis, by reversing ultra-violet radiation induced damage [ 46 ]. In the present study, we investigated the direct antiproliferative activity of L. paracasei AGR 4 against the human melanoma cell line, A375, employing the SRB assay.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to UV radiation-induced skin damage, the efficiency of probiotics such as Lactobacillus johnsonii NCC 533 (La1) has been demonstrated. The absorption of L. johnsonii was shown to reinforce cutaneous immune system homeostasis by preventing the increase in interleurkin-10 generated by UVs and to decrease the recruitment of epidermal Langerhans cells [ 75 , 76 ]. In the same way, the administration of a probiotic strain of Lactobacillus rhamnosus GG (LGG) was demonstrated to prevent the development of skin tumors thanks to the activity of its lipoteichoic acid (LTA), a component of the Gram-positive bacteria cell wall.…”
Section: Photoprotectionmentioning
confidence: 99%
“…In a murine model, LTA decreased UV-induced skin immunosuppression and thus significantly reduced UV-induced skin tumor growth [ 74 ]. Other photoprotective candidates can be considered, such as Lactobacillus plantarum HY7714, Bifidobacterium breve and Bifidobacterium longum [ 75 , 77 , 78 ]. These observations are promising but need to be confirmed in humans.…”
Section: Photoprotectionmentioning
confidence: 99%
“…Although different from radiation injury, the microbiome research conducted for other skin injuries, such as those involving ultraviolet irradiation ( Wolf et al, 2016 ; Patra et al, 2019 ; Patra et al, 2020 ), diabetic ulcers, and other chronic skin diseases ( Wolcott et al, 2016 ; Johnson et al, 2018 ), may shed light and help guide future skin microbiome research in the context of radiation injury. Additionally, clinical strategies currently used to treat these complicated skin wounds may provide insight into identifying effective therapeutics and improving patient outcomes.…”
Section: The Effects Of Radiation On the Microbiomementioning
confidence: 99%
“…In late 2001, the Food and Agriculture Organization of the United Nations and the World Health Organization held an expert consultation in Cordoba, Argentina, to evaluate the health and nutritional properties of probiotics in food, which led to a joint report to provide assessment and safety guidelines for research in the field ( Food and Agriculture Organization of the United Nations World Health Organization, 2006 ). Since then, many studies have demonstrated the beneficial effect that live, naturally occurring microorganisms can have on the immune system ( Hardy et al, 2013 ; Peters et al, 2019 ), gut ( Gourbeyre et al, 2011 ; Quigley, 2012 ), food allergies ( Di Costanzo et al, 2020 ), colon ( Pujo et al, 2020 ; Wang et al, 2020 ), skin ( Friedrich et al, 2017 ; Patra et al, 2020 ), and central nervous system ( Kim et al, 2020 ; Loniewski et al, 2020 ). Of particular importance for this review are the therapeutic effects of probiotics that are seen when these systems are exposed to ionizing radiation.…”
Section: The Effects Of the Microbiome On The Radiation Responsementioning
confidence: 99%